Genome-Wide Association Study and Genomic Prediction for Soybean Cyst Nematode Resistance in USDA Common Bean (Phaseolus vulgaris) Core Collection - Shi, Ainong; Gepts, Paul; Song, Qijian; Xiong, Haizheng; Michaels, Thomas E.; Chen, Senyu (Frontiers in Plant Science, 2021)
Common bean (Phaseolus vulgaris) is a good host of soybean cyst nematode (SCN, Heterodera glycines), and its production is challenged by this emerging pest in many regions such as the upper Midwest USA. The objectives of this study were to evaluate the SCN-resistance in USDA common bean core collection, to conduct genome-wide association study (GWAS) to identify SNP markers associated with SCN resistance, and to perform genomic prediction (GP) for SCN resistance. A total of 315 accessions of the USDA common bean core collection were evaluated for resistance to SCN HG Type 0 (race 6). The common bean core set was genotyped with the BARCBean6K_3 Infinium BeadChips consisting of 4,654 SNPs. Results showed that 15 accessions were resistant to SCN with a Female Index (FI) at 4.8 to 9.4, and 62 accessions were moderately resistant (10 < FI < 30) to HG Type 0. The association study showed that 11 SNP markers, located on chromosomes Pv04, 07, 09, and 11 were strongly associated with resistance to HG Type 0. GWAS was also conducted for resistance to HG Type 2.5.7 and HG Type 1.2.3.5.6.7 based on the public dataset (N=276) consisting of a diverse set of common bean accessions genotyped with the BARCBean6K_3 chip. Six SNPs associated with HG Type 2.5.7 resistance on Pv01, 02, 03, and 07, and 12 SNPs with HG Type 1.2.3.5.6.7 resistance on Pv01, 03, 06, 07, 09, 10, and 11 were detected. The accuracy of genomic prediction was 0.36 to 0.49 for resistance to the three SCN HG types, indicating that genomic selection (GS) of SCN resistance is feasible. This study provides basic information for developing SCN-resistant common bean cultivars using the USDA core germplasm accessions. The SNP markers can be used in molecular breeding in common bean through marker-assisted selection (MAS) and GS.